The experience of adolescent inpatient care and the anticipated transition to the community: Young people's perspectives. (January 2016) - Gill, Freya; Butler, Stephen; Pistrang, Nancy
Abstract: This study explored adolescents' perspectives of inpatient mental health care, focussing on aspects of the inpatient environment they anticipated would help or hinder their transition back home. Semi-structured interviews were conducted with 12 adolescent inpatients; transcripts were analysed thematically. Participants experienced inpatient treatment as offering a mix of benefits (e.g., supportive relationships) and drawbacks (e.g., living in a "fake world"). They anticipated the transition home as providing opportunities for personal growth and consolidation of new coping skills, but also posing challenges concerning re-entering the "real world" after the experience of being "wrapped in cotton wool". Self-determination theory and attachment theory offer two potential frameworks for understanding these opportunities and challenges. Inpatient care has the potential to foster key mechanisms for adaptive development, creating a platform for developing positive future behaviours. Community teams should work closely with inpatient units to support the generalisation of the young person's newly acquired coping skills.